The child sex scandal and modern Irish literature: writing the unspeakable - Valente, Joseph (Irish culture, memory, place, 2020)
Introduction: The enigmatic history of imperiled innocence -- "An iridescence difficult to account for" : sexual initiation in Joyce's fiction of development -- Between (open) secret and enigma : Kate O'Brien, The land of spices, and the stylistic invention of lesbian (in)visibility -- Country girl : groomed, seduced, and abandoned -- From the pits and ditches where people have fallen : sex scandal and the reinvention of the Irish public sphere in Keith Ridgway's The long falling -- Retrofitting Ireland's architecture of containment in Tana French's In the woods -- "Roaring inside me" : the enigma of sexual violence in The gathering -- Epilogue: What about Brendan?